The source of the power of (tradition) in law - فاروق (Sulaimani Journal for Humanities, 2001)
The custom is the extension of a group of achieving some actions or speech in a special way with the convince of that group by the importance of the achievement of that action and speech by the special way been achieved. Custom by its legal mean based on two basics: First: the material basic which is the multiplication of that action or speech. Second: convince of that group of the importance of considering that custom in such away that if they did not achieve it they will be legally punished. In this research we will question what the source of the force of custom? Is it the essence of Custom and its benefit it gives to the people and provision of their demands? Or custom's force is coming from the court of law? or the legislator gives it the force? The legalist have different opinion's about that matter, some of them are saying that the conscience of the group and some say that it is the court of law and other's say that it is the legislator. After the presentation of those idea's and opinions and discussion made on their essence we reached the result that the essence of custom it self is the source of it's power by the meaning that the good opinion of the society for that action or speech (which become a custom) reforms the custom and makes it real, but the demand of the legislator is as a monitor while it sees that the custom is useful he legislates it inclusively and anytime it accepted the custom in the place of the custom he establishes a legal form (commanding) in which the custom is no longer active, so the essence of the custom and the demand of the legislator are the source of the force of the custom, this is because of that the demand of the legislator is educated and considering the demands of the society but the demand of a society may direct to a private benefit, and this is why the legal force is not awarded to a the (Custom) only and in the law the written lav (legislation) is ahead of (custom) as a legal sourc.